Analisis Transmisi dan Pembentukan Harga Beras di Provinsi Jawa Tengah - Manurung, Ferdi; Handayani, Migie; Setiyawan, Hery (Universitas Galuh, 2026)
Rice is one of the agricultural commodities that plays an important role in Indonesia's food security because it is the main staple food for the community. The role of rice as a strategic agricultural commodity in Central Java and as one of the largest rice production centers in Indonesia means that changes in rice prices have a significant impact on the economy and welfare of both farmers and consumers. Rice price movements in Central Java Province, both at the farmer and consumer levels, experience fluctuations. Fluctuations in rice prices are caused by several factors that affect rice prices in Central Java. The research method used is the Secondary Data Analysis (SDA) method. The type of data used is time series data for the period January 2014 - December 2022. The data used is monthly data on grain prices at the farmer level and rice prices at the consumer level. Data analysis was conducted using the AECM (Asymmetric Error Correction Model) method to analyze price transmission patterns. The results of the causality test showed that consumer rice prices influence the formation of corn prices at the producer level. The results of the study indicate that the rice price transmission pattern in Central Java Province is asymmetric in the short term, meaning that consumer prices in the same period are not immediately transmitted to prices at the farmer level.